Sustainable coastal and maritime tourism: A potential blue economy avenue for Bangladesh - Md Wasiul Islam; Tapan Sarker (Asian Development Bank Institute (ADBI), 2021)
The geographic and strategic location of Bangladesh besides the Bay of Bengal has opened up multidimensional opportunities for the development of coastal and maritime tourism (CMT). Though various legal documents and researchers have already detected opportunities for CMT from the perspective of Bangladesh, there is scant evidence of any systematic research on the institutional arrangements influencing the prospect of the development and promotion of CMT in Bangladesh. The status of the socio-cultural, economic, environmental, and institutional perspectives on the coastal and marine zones of Bangladesh warrants an in-depth study focusing on the institutional arrangements that can support sustainable CMT in Bangladesh. Therefore, this study examines the institutional arrangements to identify the prospects and challenges involved in developing sustainable CMT in Bangladesh. In particular, the study appraises the existing institutions supporting sustainable CMT and suggests policy guidelines to develop sustainable CMT policy and practice in Bangladesh. Moreover, this qualitative study considers how sustainable CMT can potentially influence the blue economy, which can enhance poverty reduction through new job creation, biodiversity conservation, environmental pollution control, and the promotion of the sustainable use of coastal and marine natural resources. The study aims to draw some useful policy guidelines for policy makers to intensify their emphasis on sustainable CMT as an avenue to promote the blue economy and facilitate a better living standard for coastal zone communities.
Keywords: L83; Z32; Z39; 330; Coastal and maritime tourism; blue economy; sustainable development; institutions; natural resources; Bangladesh